Construction and evaluation of multi=trait selection indices fOr overall economic improvement in White Legborn layers - NIRANJAN, S; SINGH, HARPAL; KRISHNA, S T (The Indian Journal of Animal Sciences, 2013)
Data collected on 1922 pullets produced in 3 hatches hy mating 48 sires with 324 darns forage at sexual maturity, egg production up to 280 days of age, 32 weeb egg weights: body weight at 20 and 40 weeks of age were used for computation of multi-trait selection indices. On the hasis of values, and cxpected genetic gains (H), index I wherein all the 5 traits were incorporated was most efficient, among the 26 selection indices evaluated. On the has is of reduction in rHl values, due to non-inclusion of different traits in the index, 40-weck body weight, 20-week body weight, 32-week egg weight, egg production up to 280 days of age and age at sexual maturity were found 10 be important in that order.